The November man [videorecording (DVD)] - Granger, Bill; Brosnan, Pierce; Bracey, Luke, 1989-; Patton, Will; Kurylenko, Olga, 1979- ([Publisher not identified], 2014)
Codenamed 'The November Man,' Peter Devereaux is a lethal and highly trained ex-CIA agent who has been enjoying a quiet life in Switzerland. When Devereaux is lured out of retirement for one last mission, he must protect valuable witness Alice Fournier. He soon finds this assignment makes him a target of his former friend and CIA protege David Mason. With growing suspicions of a mole in the agency, there is no one Devereaux can trust, no rules, and no holds barred.